Prevention of Anarchist Demonstrations through Character Education in University - Dedy Indriyanto; Liliana Tedjosaputro; Totok Tumangkar; Fania Mutiara Savitri (Universitas Serambi Mekkah, 2022)
The phenomenon of demonstrations carried out by students is no longer an unusual thing but has become a habit. Social problems in the name of society make students the vanguard to protect, but not a few of them carry out anarchist actions. This requires prevention by means of an educational approach that not only emphasizes the teaching dimension alone, but also on the human and educational dimensions that have character. This study aims to analyze the causes of student anarchism during demonstrations and to analyze character-based education applied at UIN Walisongo in preventing anarchism during demonstrations. The case study in this research is the prevention of anarchist demonstrations at UIN Walisongo Semarang based on character education. This study used a descriptive qualitative method with several informants including the head of the Central Java Police Mobile Brigade Unit, Lecturer at UIN Walisongo State Islamic University and the Community. The results of this study prove that the main cause of demonstrations turning into anarchy according to the interview results is because the masses are provoked. Another factor was due to the unsatisfactory handling and not being allowed to enter for discussions so that it could be said to have violated the demonstrators' human rights. Character-based education that must be implemented includes concepts in introducing and explaining to students about values issues, making judgments on facts, social behavior approaches to assessing; measuring good character, cognitive approach and affective approach. The research implication lies in minimizing the factors that cause student anarchism and including character education as a university subject, for example in civics education courses. Keywords: Demonstration, Prevention of Anarchy, Character Education.